The Effect of the Implementation of Risk Management and Corporate Governance with Profit Management as a Variable Intervening On the Financial Performance of Banking (Analytical Study on Commercial Banking Listed On the Indonesia Stock Exchange) - Khalisah Visiana; Aulia Friska Febianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine whether Risk Management and Corporate Governance with earnings management as an intervening variable on the financial performance of banking companies listed on the IDX, to determine whether Risk Management and Corporate Governance affect the financial performance of banking companies. IDX listed earnings management as an intervening variable to determine whether Risk Management and Corporate Governance affect earnings management in banking companies listed on the IDX and whether earnings management affects earnings management. On the financial performance of banking companies listed on the IDX. The population used in this study were 43 banking companies listed on the Indonesia Stock Exchange. Using the purposive sampling method, there were 20 selected banking companies. Using 2016 to 2020 (5 years) observation years but measuring discretionary accrual plus the 2015 observation year will get 100 data observations as sampling in this study. Hypothesis testing is done by linear regression analysis. From the results of hypothesis testing, it is known that the application of risk management has no significant effect on financial performance and corporate governance has no significant effect on financial performance. Moreover, applying risk management using earnings management as an intervening variable cannot mediate financial performance. Applying corporate governance using earnings management as an intervening variable cannot mediate company performance, meaning that earnings management is not a good variable in mediating the relationship between risk management, Corporate Governance with Financial Performance (KK), and Risk Management have an effect on earnings management. In contrast, Corporate Governance does not affect earnings management, and earnings management does not affect financial performance.